Die Vergnügungen der anderen: Fachsensible Hochschuldidaktik als neuer Weg zwischen allgemeiner und fachspezifischer Hochschuldidaktik - Scharlau, Ingrid; Keding, Gesche (Pädagogische Hochschulentwicklung: von der Programmatik zur Implementierung)

Sich gar nicht erst im behaglichen Zuhause der eignen Disziplin einrichten: Eine fachfremde Hausarbeit im ersten Semester - Scharlau, Ingrid; Heß, Christiane (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

And now for something completely different - Lehren und Lernen angesichts digitaler Herausforderungen - Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Mathematik schreiben - Scharlau, Ingrid (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2014)

Drei Einflüsse auf Schreibberatung und ein integriertes Modell der Selbststeuerung für Schreibberaterinnen und Schreibberater - Keding, Gesche; Scharlau, Ingrid (Schreibberatung und Schreibförderung. Impulse aus Theorie, Empirie und Praxis)

Reading mathematical texts with philosophical methods - Schnieder, Jörn; Scharlau, Ingrid (Special Issue: The Philosophy of Mathematics Education at ICME 13)
The paper presents a hermeneutic approach to teaching and learning mathematics in which the hermeneutic circle is translated into methods of reading mathematical texts with the help of the three decisive steps 1) making prior knowledge explicit, 2) interpreting texts, and 3) fusing horizons of prior understanding and text content.

Zwei Fenster mit verschiedener Sicht - Scharlau, Ingrid; Karsten, Andrea; Nettingsmeier, Pia; Golombek, Christiane; Schäfer, Stefanie (Akademisches Schreiben. Halbband 1: Vom Qualitätspakt Lehre geförderte Schreibzentren und Schreibwerkstätten)

Does attention speed up processing? Decreases and increases of processing rates in visual prior entry. - Tünnermann, Jan; Petersen, Anders; Scharlau, Ingrid (Journal of Vision)
Selective visual attention improves performance in many tasks. Among others, it leads to 'prior entry'—earlier perception of an attended compared to an unattended stimulus. Whether this phenomenon is purely based on an increase of the processing rate of the attended stimulus or if a decrease in the processing rate of the unattended stimulus also contributes to the effect is, up to now, unanswered. Here we describe a novel approach to this question based on Bundesen’s Theory of Visual Attention, which we use to overcome the limitations of earlier prior-entry assessment with temporal order judgments (TOJs) that only allow relative statements regarding the processing speed of attended and unattended stimuli. Prevalent models of prior entry in TOJs either indirectly predict a pure acceleration or cannot model the difference between acceleration and deceleration. In a paradigm that combines a letter-identification task with TOJs, we show that indeed acceleration of the attended and deceler
Keywords: unattended stimuli; attention speed; cognitive processing; Attention; Humans; Judgment; Mental Recall; Visual Perception; Stimulus Parameters; Visual Perception; Visual Attention; Cognitive Processes; Velocity

Fachsensible Hochschuldidaktik - Scharlau, Ingrid (Teaching is touching the future: Academic teaching within and across disciplines)

Nur Zahlen und Zeichen? Zum Nutzen des Schreibens in der Hochschuldidaktik der Mathematik - Scharlau, Ingrid; Heß, Christiane; Schnieder, Jörn (Neues Handbuch Hochschullehre. 70. Ergänzungslieferung)

Reflection on the Leitmotif "Wrapped in Code" - Scharlau, Ingrid

Schreiben im Blick. Schriftliche Formen der sprachlichen Tätigkeit aus dialogischer Perspektive - Karsten, Andrea

Writing: Movements of the self - Karsten, Andrea (Theory & Psychology)
This article presents analyses of excerpts from a study on writing conducted in a dialogical perspective. The study’s material was collected by the auto-confrontation method: writers were videotaped during their work and afterwards confronted with their writing activities. Microanalysis of the material attends to how inner dialogues during writing are “refracted” (Voloshinov) in auto-confrontation. Bakhtin’s notion of the chronotope (time-and-space) as the main tool of analysis helps to discern the changing contexts and position constellations utterances are valid for. It thus sheds light on the positioning movements performed by the writing selves through language. The analyses show various utterance movements traversing the chronotopes involved, ranging from refractions of movements between the writers’ inner dialogues and their texts to retrospective imperatives with a developmental potential. This “dialogical volume” of speech activity presenting itself in writing can contribute to our understanding of the interplay of language and the self.
Keywords: auto-confrontation; chronotope; inner dialogue; microanalysis; positioning; writing

Schreiben ist Dialog. Ergebnisse und Implikationen einer Studie zum ,schreibbegleitenden‘ Sprechen - Karsten, Andrea (JoSch – Journal der Schreibberatung)

Erwerb mathematischer Schreibkompetenz während der Studieneingangsphase - Scharlau, Ingrid; Schnieder, Jörn (Beiträge zum Mathematikunterricht 2014)

Textilien - Eine Beobachtung - Scharlau, Ingrid (Kleppart - Ausstellungen 2010-2013)

Humboldt revisited - forschend lehren - lehrend forschen - Keding, Gesche; Scharlau, Ingrid (Greifswalder Beiträge zur Hochschullehre: Forschendes Lehren und Lernen in der polyvalenten Lehre)

Jean Piaget zur Einführung - Scharlau, Ingrid

Studium und Beruf: Studienstrategien - Praxiskonzepte - Professionsverständnis. Perspektiven von Studierenden und Lehrenden nach der Bologna-Reform

Schreiben: Tipps, Anregungen und Strategien für das Schreiben am Leuphana College - Scharlau, Ingrid; Heß, Christiane; Vierck, Sigrid; Bluhm, Clara

Self-Assessment-Instrumente: Eine Möglichkeit der Bildung, Reflexion und Ausdifferenzierung von Subjektiven Theorien - Scharlau, Ingrid; Bunte, Nicola; Wiescholek, Sabrina (Studium und Beruf: Studienstrategien - Praxiskonzepte – Professionsverständnis. Perspektiven von Studierenden und Lehrenden nach der Bologna-Reform)
Unter Bezugnahme auf Erkenntnisse, die im Rahmen des Projekts STEP (Studium und Beruf: Subjektive Theorien von Studierenden und Lehrenden zwischen Praxisbezug, Employability und Professionalisierung) gewonnen wurden, wird nach der Möglichkeit der Bildung, Reflexion und Ausdifferenzierung von Subjektiven Theorien durch Self-Assessments gefragt. Inhalte wie Strukturiertheit und Theorieförmigkeit der Vorstellungen (Vernetzungen, schlussfolgernd-argumentativer Charakter) erwiesen sich in der Untersuchung als deutlich veränderungsbedürftig. Es wird argumentiert, dass eine inhaltliche Anreicherung oder Restrukturierung vorhandener Überzeugungen die Ausbildung großer und komplexer Überzeugungssysteme vorausetzt. Maßnahmen, die an den individuellen Vorstellungen, deren Bewusstmachung und Reflexion ansetzen, werden vorgestellt.

A New Model of Higher Education in the European Context - The Leuphana Experience - Gunkel, Marjaana; Schütz, Julia; Seifert, Andreas; Scharlau, Ingrid; Beck, Karin; Heuer, Claudia (INTED2013 Conference Proceedings)

Ringen um Sinn. Subjektive Theorien von Lehramtsstudierenden zum Praxisbezug des Studiums. - Scharlau, Ingrid; Wiescholek, Sabrina (Studium und Beruf: Studienstrategien - Praxiskonzepte - Professionsverständnis. Perspektiven von Studierenden und Lehrenden nach der Bologna-Reform)

Was also ist gleichzeitig? Allgemeinpsychologische Anmerkungen zur Wahrnehmung von Gleichzeitigkeit - Scharlau, Ingrid; Weiß, Katharina (Simultaneität)

Attention and the Speed of Information Processing: Posterior Entry for Unattended Stimuli Instead of Prior Entry for Attended Stimuli - Weiß, Katharina; Hilkenmeier, Frederic; Scharlau, Ingrid (PLoS ONE)
Why are nearly simultaneous stimuli frequently perceived in reversed order? The origin of errors in temporal judgments is a question older than experimental psychology itself. One of the earliest suspects is attention. According to the concept of prior entry, attention accelerates attended stimuli; thus they have “prior entry” to perceptive processing stages, including consciousness. Although latency advantages for attended stimuli have been revealed in psychophysical studies many times, these measures (e.g. temporal order judgments, simultaneity judgments) cannot test the prior-entry hypothesis completely. Since they assess latency differences between an attended and an unattended stimulus, they cannot distinguish between faster processing of attended stimuli and slower processing of unattended stimuli. Therefore, we present a novel paradigm providing separate estimates for processing advantages respectively disadvantages of attended and unattended stimuli. We found that deceleration of unattended stimuli contributes more strongly to the prior-entry illusion than acceleration of attended stimuli. Thus, in the temporal domain, attention fulfills its selective function primarily by deceleration of unattended stimuli. That means it is actually posterior entry, not prior entry which accounts for the largest part of the effect.

Prior entry and temporal attention: Cueing affects order errors in RSVP. - Hilkenmeier, Frederic; Olivers, Christian N. L.; Scharlau, Ingrid (Journal of Experimental Psychology: Human Perception and Performance)
The law of prior entry states that attended objects come to consciousness more quickly than unattended ones. This has been well established in spatial cueing paradigms, where two task-relevant stimuli are presented near-simultaneously at two different locations. Here, we suggest that prior entry also plays a pivotal role in temporal attention paradigms, where stimuli appear at the same location but at distinct moments in time, in rapid serial presentation (RSVP). Specifically, we hypothesize that prior entry can explain temporal order reversals in reporting two targets from RSVP. In support of this, three experiments show that cueing attention toward either of the targets has a strong influence on order errors. We conclude that prior entry provides a viable explanation of the way in which relevant information is prioritized in RSVP. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: attentional blink; attentional enhancement; lag-1 sparing; prior entry; temporal cueing; visual attention; rapid serial presentation; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Female; Humans; Male; Neuropsychological Tests; Pattern Recognition; Visual; Time Factors; Visual Perception; Young Adult; Cues; Serial Recall; Visual Attention; Eyeblink Reflex

At the mercy of prior entry: Prior entry induced by invisible primes is not susceptible to current intentions. - Weiß, Katharina; Scharlau, Ingrid (Acta Psychologica)
If one of two events is attended to, it will be perceived earlier than a simultaneously occurring unattended event. Since 150 years, this effect has been ascribed to the facilitating influence of attention, also known as prior entry. Yet, the attentional origin of prior-entry effects¹ has been repeatedly doubted. One criticism is that prior-entry effects might be due to biased decision processes that would mimic a temporal advantage for attended stimuli. Although most obvious biases have already been excluded experimentally (e.g. judgment criteria, response compatibility) and prior-entry effects have shown to persist (Shore, Spence, & Klein, 2001), many other biases are conceivable, which makes it difficult to put the debate to an end. Thus, we approach this problem the other way around by asking whether prior-entry effects can be biased voluntarily. Observers were informed about prior entry and instructed to reduce it as far as possible. For this aim they received continuous feedback
Keywords: intentions; events; attention; decision processes; Adult; Attention; Choice Behavior; Cues; Female; Humans; Intention; Judgment; Male; Middle Aged; Reaction Time; Time Perception; Visual Perception; Attention; Decision Making; Experiences (Events); Intention

Spatial mislocalization as a consequence of sequential coding of stimuli. - Priess, Heinz-Werner; Scharlau, Ingrid; Becker, Stefanie I.; Ansorge, Ulrich (Attention, Perception, & Psychophysics)
In three experiments, we tested whether sequentially coding two visual stimuli can create a spatial misperception of a visual moving stimulus. In Experiment 1, we showed that a spatial misperception, the flash-lag effect, is accompanied by a similar temporal misperception of first perceiving the flash and only then a change of the moving stimulus, when in fact the two events were exactly simultaneous. In Experiment 2, we demonstrated that when the spatial misperception of a flash-lag effect is absent, the temporal misperception is also absent. In Experiment 3, we extended these findings and showed that if the stimulus conditions require coding first a flash and subsequently a nearby moving stimulus, a spatial flash-lag effect is found, with the position of the moving stimulus being misperceived as shifted in the direction of its motion, whereas this spatial misperception is reversed so that the moving stimulus is misperceived as shifted in a direction opposite to its motion when the c
Keywords: spatial mislocalization; sequential coding; stimulus parameters; Attention; Discrimination (Psychology); Humans; Judgment; Motion Perception; Optical Illusions; Orientation; Pattern Recognition; Visual; Psychophysics; Space Perception; Cognitive Processes; Motion Perception; Perceptual Localization; Spatial Perception; Stimulus Parameters; Consequence

The dynamics of prior entry in serial visual processing. - Hilkenmeier, Frederic; Scharlau, Ingrid; Weiß, Katharina; Olivers, Christian N. L. (Visual Cognition)
An attended stimulus reduces the perceptual latency of a later stimulus at the same location, leading to the intriguing finding that the perceived order between the two is often reversed. This prior-entry effect has been well established in a number of different cueing paradigms, mostly involving spatial attentional shifts. Here we assess the time-course of prior entry when all stimuli appear in rapid serial presentation at one location. Our findings indicate that the size of the attentional enhancement is strongly affected by the stimulus onset asynchrony between cue and target, with a rapid early peak, followed by decay. When task-irrelevant cues are used, the cueing effect on prior entry is short-lived and peaks as early as 50 ms. The benefit extends to about 100 ms when task-relevant cues are employed. These results fit with a straightforward computational model of transient attentional enhancement, peaking about 80 100 ms after stimulus detection. (PsycINFO Database Record (c) 20
Keywords: serial visual processing; prior entry dynamics; cueing paradigms; Cues; Visual Perception; Visual Search

Subjektive Theorien von Musikerinnen und Musikern zum Üben: Ein Beitrag an der Schnittstelle von Kognitionspsychologie - Bunte, Nicola; Scharlau, Ingrid (Popmusikforschung und Musikpädagogik)
This article reports on the findings of a qualitative interview study that investigated the individual ideas about practicing of nine musicians of different musical backgrounds, music genres, instruments, and learning biography. The findings reveal a variety of different aspects that are embedded in argumentative reasoning, and thus are analysed as subjective theories. According to differences in complexity with regards to content and argumentative structure we propose the following typification: 1) physical-technical constriction, 2) technique and interpretation centered type, and 3) creative-congnitive focus. A strict affiliation between these types and musical genre was not found.

Praxis nach Rezept? – Praxisbezug und Professionalität in den subjektiven Theorien von Lehramtsstudierenden - Schüssler, Renate; Keuffer, Josef; Günnewig, Kathrin; Scharlau, Ingrid (Schulpädagogik heute: Reform der Lehrerbildung in Deutschland, Österreich und der Schweiz)

Psychologie in der Lehrerbildung: Didaktische Konzeption zur Förderung von Conceptual Change, Selbstlern- und Reflexionskompetenz - Müsche, Hanna S.; Scharlau, Ingrid (Psychologiedidaktik und Evaluation IX)
Es wird eine psychologiedidaktische Konzeption skizziert, die vorwiegend auf der Basis empirischer Evidenz für das bildungswissenschaftliche Lehramtsstudium an der Universität Paderborn entwickelt wurde. Drei Bausteine greifen ineinander: Im Zentrum steht das problemorientierte Lernen, das durch beispielbasiertes Lernen und forschendes Lernen flankiert wird. Über die Einführung in psychologisches Wissen und Denken hinaus wird mit der Konzeption das Ziel verfolgt, die Studierenden in Conceptual Change-Prozessen, im selbstgesteuerten Lernen und in ihrer Reflexionsfähigkeit zu unterstützen und zu fördern. Insgesamt bewegt sich die Konzeption zwischen den lernpsychologischen Polen von Konstruktion und Instruktion und will sowohl einer Berufsfeldorientierung als auch einer Wissenschaftsorientierung Rechnung tragen.

Evaluierung medizinischer Volumenrendering-Algorithmen durch empirische Studien - Domik, Gitta; Arens, Stephan; Tünnermann, Jan; Scharlau, Ingrid (FIfF-Kommunikation)
Wie gut ist ein Rendering Algorithmus, der Bilder aus Daten generiert, die wiederum als Grundlage für eine medizinische Diagnose verwendet werden? In diesem Beitrag werden einerseits beispielhaft empirische Studien und ihre Ergebnisse vorgestellt, die solche Fragestellungen beantworten. Andererseits widmen wir uns auch der generellen Frage, welche Herausforderungen gemeistert werden müssen, um empirische Studien aufzustellen, die in Bezug auf korrekte medizinische Diagnosen und ihre zugrunde liegenden Rendering-Algorithmen sinnvoll sind.
Keywords: Informatik; Visualisierung; Psychologie; Experimentaldesign

Praxis nach Rezept? – Praxisbezug und Professionalität in den subjektiven Theorien von Lehramtsstudierenden - Schüssler, Renate; Keuffer, Josef; Günnewig, Kathrin; Scharlau, Ingrid (Reform der Lehrerbildung in Deutschland, Österreich und der Schweiz. Teil I: Analyse, Perspektiven und Forschung)

Chronotopes in Writing. Excerpts from a Case Study. - Karsten, Andrea (Tätigkeitstheorie – Journal für tätigkeitstheoretische Forschung in Deutschland (Activity Theory – Journal of Activity-Theoretical Research in Germany))

Wie sehen Studierende das Verhältnis von Studium und Beruf? Praxisbezug und Professionalität in den Subjektiven Theorien Studierender - Oechsle, Mechthild; Scharlau, Ingrid; Hessler, Gudrun; Günnewig, Kathrin (Der Bologna-Prozess aus Sicht der Hochschulforschung)
Der Beitrag befasst sich mit der Frage, auf welche Weise Studierende die Anforderungen von Wissenschaft und Berufspraxis aufeinander beziehen und welche Subjektiven Theorien sie hierzu entwickeln. Basierend auf einer qualitativen Befragung von Studierenden des Lehramts und der Soziologie rekonstruiert der Beitrag verschiedene Konzepte von Praxisbezug und Professionalität und analysiert mögliche Zusammenhänge zwischen diesen Konzepten. Der Beitrag macht deutlich, dass es neben der (erwartbaren) Heterogenität zwischen den Studiengängen eine erhebliche Heterogenität der entsprechenden Subjektiven Theorien innerhalb der jeweiligen Studiengänge gibt und diskutiert mögliche Schlussfolgerungen für die universitäre Lehre.

Self-Assessment-Instrumente: Eine Möglichkeit der Reflexion und Differenzierung von Subjektiven Theorien - Scharlau, Ingrid (Workshop: Zum Verhältnis von Studium und Berufspraxis. Perspektiven von Lehrenden und Studierenden)

Top-down contingent feature-specific orienting with and without awareness of the visual input. - Ansorge, Ulrich; Horstmann, Gernot; Scharlau, Ingrid (Advances in Cognitive Psychology)
In the present article, the role of endogenous feature-specific orienting for conscious and unconscious vision is reviewed. We start with an overview of orienting. We proceed with a review of masking research, and the definition of the criteria of experimental protocols that demonstrate endogenous and exogenous orienting, respectively. Against this background of criteria, we assess studies of unconscious orienting and come to the conclusion that so far studies of unconscious orienting demonstrated endogenous feature-specific orienting. The review closes with a discussion of the role of unconscious orienting in action control. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual input; awareness; conscious; orientation; visual perception; Awareness; Consciousness States; Perceptual Orientation; Visual Perception; Blindsight

Prior entry explains order reversals in the attentional blink. - Olivers, Christian N. L.; Hilkenmeier, Frederic; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
When two targets are presented in rapid succession, the first target (T1) is usually identified, but the second target (T2) is often missed. A remarkable exception to this 'attentional blink' occurs when T2 immediately follows the first T1, at lag 1. It is then often spared but reported in the wrong order—that is, before T1. These order reversals have led to the hypothesis that 'lag 1 sparing' occurs because the two targets merge into a single episodic representation. Here, we report evidence consistent with an alternative theory: T2 receives more attention than T1, leading to prior entry into working memory. Two experiments showed that the more T2 performance exceeded that for T1, the more order reversals were made. Furthermore, precuing T1 led to a shift in performance benefits from T2 to T1 and to an equivalent reduction in order reversals. We conclude that it is not necessary to assume episodic integration to explain lag 1 sparing or the accompanying order reversals. (PsycINFO Dat
Keywords: attentional blink; order reversals; prior entry; working memory; visual attention; attentional performance; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Discrimination (Psychology); Female; Humans; Male; Memory; Short-Term; Pattern Recognition; Visual; Psychophysics; Reaction Time; Reversal Learning; Sensory Gating; Serial Learning; Young Adult; Eyeblink Reflex; Stimulus Change; Stimulus Parameters; Visual Attention; Attentional Blink; Short Term Memory

Simultaneity and temporal order perception: Different sides of the same coin? Evidence from a visual prior-entry study. - Weiß, Katharina; Scharlau, Ingrid (The Quarterly Journal of Experimental Psychology)
Attended stimuli are perceived as occurring earlier than unattended stimuli. This phenomenon of prior entry is usually identified by a shift in the point of subjective simultaneity (PSS) in temporal order judgements (TOJs). According to its traditional psychophysical interpretation, the PSS coincides with the perception of simultaneity. This assumption is, however, questionable. Technically, the PSS represents the temporal interval between two stimuli at which the two alternative TOJs are equally likely. Thus it also seems possible that observers perceive not simultaneity, but uncertainty of temporal order. This possibility is supported by prior-entry studies, which find that perception of simultaneity is not very likely at the PSS. The present study tested the percept at the PSS in prior entry, using peripheral cues to orient attention. We found that manipulating attention caused varying temporal perceptions around the PSS. On some occasions observers perceived the two stimuli as sim
Keywords: temporal order perception; simultaneity; temporal order judgment; attention; visual perception; Adolescent; Adult; Attention; Cues; Discrimination (Psychology); Female; Humans; Judgment; Male; Models; Psychological; Photic Stimulation; Reaction Time; Time Factors; Uncertainty; Visual Perception; Young Adult; Attention; Judgment; Stimulus Similarity; Time Perception; Visual Discrimination; Temporal Order (Judgment)

Towards Cultural-Historical and Dialogical Writing Research – Some Methodological Considerations - Karsten, Andrea (Cultural-Historical Psychology)
Based on a cultural-historical and dialogical conceptualization of thinking and speech as formulated in Soviet psychology and linguistics of the 1920s and 1930s, this article seeks to reflect upon a congruent way of investigating writing as a cognitive and communicative activity. What has to be taken into account when developing a methodology for writing research from a cultural-historical and dialogical perspective? Firstly, writing is not separated from other forms of speech activity like interpersonal and intrapersonal speech. Thus, inner dialogue and the addressed character of writing become crucial notions to be methodologically considered. Secondly, contrary to current writing research traditions such as literacy studies and studies of the writing process in cognitive psychology, both individual writing processes and socio-cultural writing practices as well as their relationship must be considered. These reflections lead towards the conclusion that writing is not fully accessible to external observation or to introspection. In consequence, a suggestion of a methodological approach is given, inspired by the activity theoretically informed method of auto-confrontation. The proposed method consists of two phases: a) videotaping of a writing episode and b) co-analysis of the videotaped writing episode in dialogue between writer and researcher. The second phase transfers the writing activity into a new context where understanding it becomes possible. The co-analysis makes involved positions audible: positions of the writer and of the researcher, of real and imagined readers as well as intersubjective and community-related positions. Finally, implications of the proposed research setting are discussed and evaluated with regard to the theoretical grounding. An instance of the methodology to be sketched in this article was developed in the context of the author’s dissertation project in preparation at Ludwig-Maximilians-Universität in Munich, Germany with the working title «Writing processes and writing practices. A conceptualization from a dialogical perspective». The project is funded by scholarships of Universität Bayern e.V. and Ludwig-Maximilians-Universität.
Keywords: writing; writing research; dialogue; dialogical perspective; auto-confrontation

Konzeption von Schreiben - Karsten, Andrea (Tätigkeitstheorie – Journal für tätigkeitstheoretische Forschung in Deutschland (Activity Theory – Journal of Activity-Theoretical Research in Germany))
Ziel dieses Beitrags ist, Vygotskijs Konzeption von Schreiben durch eine genaue Lektüre seiner Texte herauszuarbeiten. Es zeigen sich mit einer entwicklungspsychologischen Herangehensweise zum einen und dem Begriff des schriftlichen Sprechens im Kontext von innerem und äußerem Sprechen zum anderen zwei wesentliche Interessens- und Arbeitsgebiete Vygotskijs im Hinblick auf Schreiben. Dem folgend arbeitet dieser Beitrag zunächst die Überlegungen Vygotskijs zu ontogenetischen Aspekten des Schreibens heraus. Darüber hinaus wird dargestellt, in welcher Beziehung bei Vygotskij „schriftliches Sprechen“ zu den Konzepten des inneren und des äußeren Sprechens steht. Es ergibt sich ein Bild von Schreiben als gleichermaßen kognitivem wie kommunikativem Vorgang. Auf diesen Gedanken Vygotskijs bauen abschließend Überlegungen auf, die Wege für mögliche Weiterentwicklungen von Vygotskijs Konzeption von Schreiben weisen.

Enhancing implicit change detection through action. - Tseng, Philip; Tuennermann, Jan; Roker-Knight, Nancy; Winter, Dorina; Scharlau, Ingrid; Bridgeman, Bruce (Perception)
Implicit change detection demonstrates how the visual system can benefit from stored information that is not immediately available to conscious awareness. We investigated the role of motor action in this context. In the first two experiments, using a one-shot implicit change detection paradigm, participants responded to unperceived changes either with an action (jabbing the screen at the guessed location of a change) or with words (verbal report), and sat either 60 cm or 300 cm (with a laser pointer) away from the display. Our observers guessed the locations of changes at a reachable distance better with an action than with a verbal judgment. At 300 cm, beyond reach, the motor advantage disappeared. In experiment 3, this advantage was also unavailable when participants sat at a reachable distance but responded with hand-held laser pointers near their bodies. We conclude that a motor system specialized for real-time visually guided behavior has access to additional visual information.
Keywords: implicit change detection; action perception; visual system; perceptual judgment; verbal fluency; Analysis of Variance; Awareness; Female; Humans; Male; Psychomotor Performance; Random Allocation; Reaction Time; Visual Perception; Visual Memory; Visual Stimulation; Implicit Memory; Judgment; Perceptual Discrimination

Temporal order judgments: A sensitive measure for measuring perceptual latency? - Weiß, Katharina; Scharlau, Ingrid (Proceedings of the 26th Annual Meeting of the International Society for Psychophysics)
Temporal order judgments (TOJs) have been used for demonstrating the facilitating effect of attention on information processing - prior entry. Prior entry is a robust, often large effect. Besides attention, other factors shorten perceptual latency, for instance stimulus saliency, action affordances of an object, or threatening objects. The expectable size for these effects is far smaller than that usually obtained for prior entry. Some effects might consist of only a few milliseconds. But are TOJs sensitive enough for detecting such small effects? For answering this question, we tested whether objects highly associated with a certain color are perceived earlier. In a four-alternative TOJ, including a "simultaneous" and "uncertain" category, we found a small advantage for high color diagnostic objects. This indicates high sensitivity of the TOJ task. We also found that "simultaneous" judgements were most sensitive. This is important for the debate on the usefulness of order vs. simultaneous judgments.

Top–down contingent attentional capture during feed-forward visual processing. - Ansorge, Ulrich; Horstmann, Gernot; Scharlau, Ingrid (Acta Psychologica)
Comments on an article by Jan Theeuwes (see record [rid]2010-20897-002[/rid]). Theeuwes summarizes an impressive number of studies demonstrating interference by irrelevant visual singletons in computer experiments with humans. Theeuwes assumes that this salience-driven capture of attention is fast and occurs within 150 ms since singleton onset, during the feed-forward phase of visual processing. In contrast to Theeuwes, we think that top–down contingent capture is the rule and explains initial and fast attention capture effects in the first feed-forward phase of visual processing. During a later phase and under some conditions exogenous capture of attention possibly follows. At the same time, we propose that the evidence presented by Theeuwes fails to support exogenous orienting because it fails to exclude a top–down contingent capture explanation. We present our arguments in two sections. One major source of evidence for top–down controlled attentional capture during the feed-forward
Keywords: visual selection; attention; information; visual field; brain; Attention; Humans; Models; Psychological; Visual Perception; Volition; Brain; Visual Field; Visual Perception; Visual Attention; Information

Rapid allocation of temporal attention in the attentional blink paradigm. - Hilkenmeier, Frederic; Scharlau, Ingrid (European Journal of Cognitive Psychology)
How fast can information of a first target (T1) in a rapid serial visual presentation be used for top-down allocation of attention in time? A valid cue about the temporal position of a second target (T2) was integrated into T1. The data show that 100 ms after T1 onset, T2 was identified better than without cue, raising the conditional T2 performance. T1 apparently triggers a facilitative effect of attention, known from other paradigms such as peripheral cueing. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: temporal attention; attentional blink paradigm; first target information; top-down allocation; rapid serial visual presentation; Stimulus Presentation Methods; Visual Stimulation; Visual Attention

Vielfalt des Schreibens. Zur Dialogizität schriftlicher Äußerungen im Spannungsfeld von Konventionalisierung und Positionierung - Karsten, Andrea

Jean Piaget, Die Entwicklung der physikalischen Mengenbegriffe beim Kinde: Erhaltung und Atomismus - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Jean Piaget, Das Erwachen der Intelligenz beim Kinde - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Early Top-Down Influences in Control of Attention: Evidence from the Attentional Blink - Hilkenmeier, Frederic; Tünnermann, Jan; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
The relevance of top-down information in the deployment of attention has more and more been emphasized in cognitive psychology. We present recent findings about the dynamic of these processes and also demonstrate that task relevance can be adjusted rapidly by incoming bottom-up information. This adjustment substantially increases performance in a subsequent task. Implications for artificial visual models are discussed.
Keywords: visuo-spatial attention; top-down control; task relevance; artificial visual attention; attentional blink